Field notes contributed by James J. Dinsmore, winter 1982-1983 - Dinsmore, James J.et al (1982)
Winter report of birds and locations contributed by James J. Dinsmore. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1982-1983. Epson - sheet feed